2010
DOI: 10.4103/0970-0358.70721
|View full text |Cite
|
Sign up to set email alerts
|

Review of therapeutic agents for burns pruritus and protocols for management in adult and paediatric patients using the GRADE classification

Abstract: To review the current evidence on therapeutic agents for burns pruritus and use the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) classification to propose therapeutic protocols for adult and paediatric patients. All published interventions for burns pruritus were analysed by a multidisciplinary panel of burns specialists following the GRADE classification to rate individual agents. Following the collation of results and panel discussion, consensus protocols are presented. Twenty-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Successful assessment and treatment of pruritus needs to be viewed in the context of a multidisciplinary approach. The scope of treatment ranges from moisturization and cooling of pruritic areas to agents acting on the central (gabapentin) or peripheral parts (cimetidine) of pruritic pathway and nonpharmaceutical therapies such as transcutaneous electrical nerve stimulation [6].…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Successful assessment and treatment of pruritus needs to be viewed in the context of a multidisciplinary approach. The scope of treatment ranges from moisturization and cooling of pruritic areas to agents acting on the central (gabapentin) or peripheral parts (cimetidine) of pruritic pathway and nonpharmaceutical therapies such as transcutaneous electrical nerve stimulation [6].…”
Section: Letter To the Editormentioning
confidence: 99%
“…Light gas balloons are also used to decorate parties, election rallies, opening ceremonies, and other public gatherings. This seemingly harmless decoration may explode and cause burns [6].…”
mentioning
confidence: 99%
“…28 Gabapentin is the first-line central agent used in pediatric patients and adult patients with burn for pruritis. 29 First study to evaluate gabapentin in patients with burns consisted of 35 children unresponsive to chlorpheniramine and trimeprazine. There was marked relief of pruritus with gabapentin.…”
Section: Burnsmentioning
confidence: 99%
“…There was marked relief of pruritus with gabapentin. 30 Goutos et al 29 found gabapentin to be 4 times more effective than chlorpheniramine (peripherally acting) in burns pruritus as monotherapy. Gabapentin was also more effective in combination therapy with two antihistamines compared to 3 antihistamines used alone.…”
Section: Burnsmentioning
confidence: 99%